2013
DOI: 10.4161/hv.25057
|View full text |Cite
|
Sign up to set email alerts
|

Dr Google

Abstract: IntroductionThe Internet currently stands out as an emerging information provider for the general public, in all subject areas including health. It continues to expand at a rapid rate, both in registered data volume and in web users.1 Increased Internet accessibility as well as the autonomy granted to the user in targeted searches have facilitated the use of the Internet tool and have opened up a new dimension in the chain of information transfer and medical advice. 2,3 Traditional sources of medical advice an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 24 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…30,35 When a Google web search was conducted for information about the HPV vaccine, the most frequent type of site to appear was a blog or forum, which often lacked complete information and adequate scientific credibility. 49 An analysis of public posts as of September 2014 about the potential association between HPV vaccination and infertility on Facebook, Google+, and Twitter found that most of the posts referenced news sites and blogs at substantially higher rates than scientific journals or health professional references. 30 (In)accuracy of content Reliable and accurate information was therefore often mixed in with inaccurate, conspiratorial, unrepresentative, and/or incomplete information.…”
Section: Negative Vs Positive Contentmentioning
confidence: 99%
“…30,35 When a Google web search was conducted for information about the HPV vaccine, the most frequent type of site to appear was a blog or forum, which often lacked complete information and adequate scientific credibility. 49 An analysis of public posts as of September 2014 about the potential association between HPV vaccination and infertility on Facebook, Google+, and Twitter found that most of the posts referenced news sites and blogs at substantially higher rates than scientific journals or health professional references. 30 (In)accuracy of content Reliable and accurate information was therefore often mixed in with inaccurate, conspiratorial, unrepresentative, and/or incomplete information.…”
Section: Negative Vs Positive Contentmentioning
confidence: 99%
“…Digital tools and new media can be exploited as means for accurately identifying information needs and effectively delivering vaccination campaigns. A number of studies have investigated the presence of vaccine information on the web, often starting from an analysis of Google search results obtained through the use of specific keywords ( 72 , 75 78 ). This approach can be useful for addressing information trends and gaps on available web pages.…”
Section: Introductionmentioning
confidence: 99%
“…This exercise is highly relevant because popular information sources, such as social media platforms (e.g., Twitter, Instagram) or internet search engines (e.g., Google Web Search TM ) often employ algorithms that cater to public preferences, potentially leading to biased or incorrect answers. 7 …”
Section: Methodsmentioning
confidence: 99%